Leadership and self-deception getting out of the box (BK life book., 2010)
"...the authors expose the facinating ways that we can bind ourselves to our true motivations and unwittingly sabatage the effectiveness of our own efforts to achieve success and happiness...drawing on the extensive correspondence the authors have received over the years, they have added a section that outlines the many ways that readers have been using [the book] to improve their lives and workplaces--areas such as team building, confilict resolution, and personal growth and development, to name a few" -- BACK COVER.